High school students ' opinions of problem solving skills - Erdem, Ali Rıza; Genç, Galip (Fırat University, 2014)
In this study, the opinions of high school students problem-solving skills were investigated. Research data , Heppner and Peterson (1982 ) developed by Şahin, Şahin and Heppner ( 1993) was translated into Turkish by the " Problem Solving Inventory " are obtained by applying . İzmir province's Bayındır population of the study consisted of high school students in the district . Is not able to reach the entire universe from high school students with cluster sampling rate of 450 high school students have been sampled. In the analysis of the data " using SPSS for Windows (Statistical Packages for Social Sciences )" package program was used . The internal consistency of the measurement instrument Cronbach's alpha reliability coefficient is r = 0, 77 . High school students' problem-solving skills and their opinions of their % 62.9 X =4.00 and " I often act like " shape

Bu çalışmada lise öğrencilerinin problem çözme becerilerine ilişkin görüşleri araştırılmıştır. Araştırmanın verileri, Heppner ve Peterson (1982) tarafından geliştirilen Şahin, Şahin ve Heppner (1993) tarafından Türkçeye çevrilen “Problem Çözme Envanteri” uygulanarak elde edilmiştir. Araştırmanın evrenini İzmir ilinin Bayındır ilçesindeki lise öğrencileri oluşturmaktadır. Evrenin tamamına ulaşmak mümkün olmadığından lise öğrencilerinden oranlı küme örnekleme yöntemiyle 450 lise öğrencisi örnekleme alınmıştır. Verilerin çözümlenmesinde “SPSS For Windows (Statistical Packages for Social Sciences)” paket programı kullanılmıştır. Ölçme aracının iç tutarlılığı Cronbach's Alpha güvenirlik katsayısı r= 0, 77’dir. Lise öğrencilerinin problem çözme becerilerine ilişkin görüşleri % 62,9 ve =4.00 ile “Sık sık böyle davranırım” şeklindedir.
LİSE ÖĞRENCİLERİNİN PROBLEM ÇÖZME BECERİLERİNE İLİŞKİN GÖRÜŞLERİ